Factors Affecting Health Expenditures of Households in Iran: Application of Ordered Probit Model - AM Ahmadi (مدیریت سلامت, 2017)
Introduction: Health expenditure, one of the households spending, is affected by family’s socio-economic status, and government health policies, such as health insurance. Therefore, this paper aimed to analyze the impact of these conditions on different levels of health expenditures of households in Iran.